Réponses

  • Omnes
  • Modérateur confirmé
2014-02-18T23:21:09+01:00
Salut,

K = ( \sqrt{5} + 4)(3 \sqrt{3} -2) = \sqrt{5} * 3 \sqrt{3} - 2*\sqrt{5} + 4 * 3 \sqrt{3} + 4 * (-2)\\
K = 3 \sqrt{5*3} - 2\sqrt{5} + 12\sqrt{3} - 8\\
K = 3 \sqrt{15} - 2\sqrt{5} + 12\sqrt{3} - 8\\
L = (3 \sqrt{2}  + 1)(3 \sqrt{15}  - 1) : (a+b)(a-b) = a^{2} -b^{2} \\
L = (3 \sqrt{2})^{2}  - 1^{2} \\
L = 9*2 - 1 =  18 - 1 = 17\\
M = (7 \sqrt{3} -2)( \sqrt{3} + 3) \\ M =  7 \sqrt{3} * \sqrt{3} + 3*7\sqrt{3} - 2\sqrt{3} -2*3\\ M = 7 \sqrt{3}^{2} + 21\sqrt{3} - 2\sqrt{3} - 6\\ % = 7*3 + 19\sqrt{3} - 6
M = 15 + 19\sqrt{3}\\

N = ( \sqrt{11}  - 1)(2 \sqrt{11}-5) \\
N =  \sqrt{11} * 2 \sqrt{11} - 5\sqrt{11}- 2 \sqrt{11}+5\\
N = 2 \sqrt{11}^{2} - 7\sqrt{11}+5\\
N = 2*11 - 7\sqrt{11}+5\\
N = 27 - 7\sqrt{11}

Exercice 47:

A = ( \sqrt{2}  +1)( \sqrt{2} -1) : (a+b)(a-b) = a^{2}  - b^{2} \\
A = \sqrt{2}^{2} - 1^{2} \\
A = 2 - 1\\
A = 1

J'espère t'avoir aidé.

Bonne soirée !